2007
DOI: 10.1136/oem.2006.029215
|View full text |Cite
|
Sign up to set email alerts
|

The recovery patterns of back pain among workers with compensated occupational back injuries

Abstract: Objectives: To investigate the longitudinal patterns of recovery among workers with compensated occupational back injuries. Methods: A longitudinal cohort study, with one-year follow-up via structured telephone interviews, among respondents off work because of ''new'' back injuries. Self-reported pain intensity was recorded at baseline and at four follow-up time points over the course of one year. Workers who answered the questionnaire on at least three occasions (n = 678) were classified into clusters accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Subgroups based on LBP trajectories have previously been identified in studies of six different cohorts [6][7][8][9][10][11]. Five of these used some sort of computerized subgrouping technique [6][7][8][9]11] and described four to five distinct LBP trajectories.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subgroups based on LBP trajectories have previously been identified in studies of six different cohorts [6][7][8][9][10][11]. Five of these used some sort of computerized subgrouping technique [6][7][8][9]11] and described four to five distinct LBP trajectories.…”
Section: Introductionmentioning
confidence: 98%
“…Five of these used some sort of computerized subgrouping technique [6][7][8][9]11] and described four to five distinct LBP trajectories. Within these studies, substantial differences between the identified subgroups indicate that the traditional use of only a population-averaged clinical trajectory may be limiting, or even distorting, our understanding of LBP.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,14 For example, Dunn et al 14 studied 342 patients from primary care with back pain over 1 year using latent class analysis. The method identified 4 clusters that differed across pain status and impact, disability, and psychological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…For example in some studies the term is used synonymously with global improvement [92], in others with improvement on various indicators such as disability [16] and return to work [69]. There is also a fundamental consideration regarding the meaning of recovery; that being whether recovery requires return to a prior health state or whether attainment of a fulfilling and satisfying life within the limitations of the condition is enough [21,80].…”
Section: Introductionmentioning
confidence: 99%